EARLINET observations of the 14–22-May long-range dust transport event during SAMUM 2006: validation of results from dust transport modelling - Müller, Detlef; Knippertz, Peter; Ansmann, Albert; Althausen, Dietrich; Tesche, Matthias; Bierwirth, Eike; Dinter, Tilman; Müller, Thomas; von Hoyningen-Huene, Wolfgang; Schepanski, Kerstin; Wendisch, Manfred; Heinold, Bernd; et al. (Tellus B: Chemical and Physical Meteorology, 2009)
We observed a long-range transport event of mineral dust from North Africa to South Europe during the Saharan Mineral Dust Experiment (SAMUM) 2006. Geometrical and optical properties of that dust plume were determined with Sun photometer of the Aerosol Robotic Network (AERONET) and Raman lidar near the North African source region, and with Sun photometers of AERONET and lidars of the European Aerosol Research Lidar Network (EARLINET) in the far field in Europe. Extinction-to-backscatter ratios of the dust plume over Morocco and Southern Europe do not differ. Ångstr¨om exponents increase with distance from Morocco. We simulated the transport, and geometrical and optical properties of the dust plume with a dust transport model. The model results and the experimental data show similar times regarding the appearance of the dust plume over each EARLINET site. Dust optical depth from the model agrees in most cases to particle optical depth measured with the Sun photometers. The vertical distribution of the mineral dust could be satisfactorily reproduced, if we use as benchmark the extinction profiles measured with lidar. In some cases we find differences. We assume that insufficient vertical resolution of the dust plume in the model calculations is one reason for these deviations.